English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I need some help to solve this math question.
Z is a complex number.
Z= a+bi
Z²=x+yi
Prove that 2x²=(a²+b²)^(1/2) +a

2006-09-24 16:15:45 · 7 answers · asked by animesongs_001 1 in Science & Mathematics Mathematics

7 answers

Z²=(a+bi)(a+bi)
Z²=a²+2abi-b²
Z²=(a²-b²)+(2ab)i
x=a²-b²
2x²=2(a²-b²)²≠(a²+b²)^(1/2) + a (see, for insance, a=1 and b=1)

So either you wrote the problem wrong or this is supposed to be some kind of trick question, because the identity you're supposed to prove does not actually hold.

2006-09-24 16:27:25 · answer #1 · answered by Pascal 7 · 0 0

Square Z:
a^2+2abi-b^2

Set it equal to Z^2:
a^2+2abi-b^2=x+iy

We know that the real parts and imaginary parts are essentially independent of each other (they satisfy equations independently) so set the real and imaginary parts equal:

a^2-b^2=x
2ab=y

So, from here, I think something in your problem is wrong. The reason I say this is because:
x^2=(a^2-b^2)^2

What you have in your problem not only has a plus sign between the two of them (which is possible but not with the other terms you have there) but also is taken the square root of (Which seems really odd). Check your problem and I'll keep an eye on the question.

I could be wrong, but something about this doesn't feel right.

2006-09-24 23:30:13 · answer #2 · answered by kain2396 3 · 0 0

Given:
Z= a + bi
Z²= x + yi
----------------
Z= a + bi
Z²= (a + bi)(a + bi)
Z²= a² + abi + abi + bi²
Z²= a² + 2abi + bi²
But i = √(-1)
→ i² = √(-1)*√(-1)
→ i² = -1
So:
Z²= a² + 2abi - b²
x + yi= a² + 2abi - b² (match up terms).
→ x = a² - b²
→ 2x = 2(a² - b²)
→ yi = 2abi
→ y = 2ab
This does not match up with what is given in the question.

2006-09-24 23:56:43 · answer #3 · answered by Brenmore 5 · 0 0

z = a+bi
z^2 = (a+bi)(a+bi) = aa - bb + 2abi
z^2 = x+yi
thus x = aa - bb
2xx = 2(aa - bb)(aa - bb) = 2a^4 + 2b^4 -4aabb
but 2xx = (aa+bb)^(1/2)+a, therefore
2a^4 + 2b^4 -4aabb = (aa+bb)^(1/2)+a
2a^4 + 2b^4 -4aabb - a = (aa+bb)^(1/2)
[1] 4(a^4 + b^4 - 2aabb - a)^2 = aa + bb,
ie, a and b satisfy [1]

2006-09-24 23:37:18 · answer #4 · answered by Eric Campos Bastos Guedes 3 · 0 0

Do the obvious multiplication of Z by itself, and collect terms. You have two expressions for Z^2, and by equating them, it should fall right out.

2006-09-24 23:27:17 · answer #5 · answered by Anonymous · 0 1

a^2-b^2+2abi=x+yi

x=a^2-b^2

y=2ab

2006-09-24 23:30:26 · answer #6 · answered by iyiogrenci 6 · 0 0

that statement is incorrect.. i tested it on z = 2+3i. please check the textbook or wherever you're getting the question from.

2006-09-24 23:28:50 · answer #7 · answered by need help! 3 · 0 0

fedest.com, questions and answers